The Role of Self-Regulatory Learning, Religiosity, and Parental Social Support with Student Academic Procrastination in Distance Learning - Azizah, Umi Fajar; Ruhaena, Lisnawati (Indigenous, 2022)
The Covid-19 pandemic has forced all face-to-face learning processes to be replaced by distance learning methods or online. The impact of distance learning is learning difficulties and decreased motivation that affect task submission. In completing coursework, an attitude that likes to procrastinate is called procrastination. This study aims to examine the relationship of self-regulation in learning, religiosity, parental social support and student academic procrastination. This study uses quantitative methods with non-experiments. The sampling technique used is simple random sampling technique and the subject is 408 college students. The measuring instrument in this study was modified with four scales, namely the Motivated Strategies for Learning Questionnaire (MSLQ), Academic Procrastination Scale (APS), The Centrality of Religiosity Scale (CRS), and Parental Social Support Scale. Data analysis used multiple regression method assisted by SPSS program. The results showed that there was a simultaneous relationship between self-regulation in learning, religiosity and parental social support and student academic procrastination in distance learning. F value of 37,585, R of 0.467 with p = 0.000 ( 0.05). Academic procrastination is influenced by self-regulation in learning, religiosity and parental social support. The contribution of self-regulation in learning to academic procrastination is 17.4%. The contribution of self-regulation in learning to academic procrastination is 17.4%.